Influence of Online Learning Platforms on Academic Performance and Student Engagement - Lilik Setiawan; Ronal Aprianto; Asma Elmar Mansurzade (International Forum of Researchers and Lecturers, 2024)
The rapid transformation of higher education driven by the advancement of digital technologies and the COVID-19 pandemic has accelerated the adoption of online learning platforms across universities worldwide. This study investigates the relationship between the use of online learning platforms, academic performance, and student engagement among university students. Using a cross-sectional survey design, data were collected from students actively participating in online learning environments to analyze how frequency of platform use influences academic outcomes and engagement levels. The results reveal a positive correlation between online learning engagement and academic performance, indicating that students who consistently participate in live sessions, complete assignments, and interact with peers and instructors achieve better academic results. Cognitive and behavioral engagement were found to be the most influential factors contributing to improved learning outcomes, while emotional engagement played a supportive role in maintaining motivation and persistence. Despite these benefits, several challenges were identified, including social isolation, limited face-to-face interaction, and technological barriers that hinder full participation. Comparisons with traditional learning environments highlight that online platforms provide greater flexibility and personalized learning opportunities but lack the immediacy of in-person interaction. Furthermore, differences between local and international contexts underscore the role of infrastructure and institutional readiness in ensuring equitable online learning experiences. The study concludes that effective integration of technology, instructor presence, and collaborative tools can enhance engagement and academic success in digital learning environments. Future research should explore long-term impacts, including the role of gamification and artificial intelligence in sustaining motivation and improving educational outcomes.